Effect of Loading Rate on Fracture Toughness Measurement of 7010 Aluminium Alloy and Mild Steel - Talib, Jamilah (2004)
The fracture toughness of structural material is a matter of vital interest in residual life and safety assessment work. Many structures in service today were erected in a time when safety requirements in terms of notch or fracture toughness were not specified. This means that often very little is known about the defect tolerance of such structures under various loading conditions. The effect of intermediate loading rates upon fracture toughness of structural material has not been widely reported compared with static or very high loading rates. In the present work, the effect of intermediate loading rates upon fracture toughness and yield strength properties of aluminium alloy 7010-T7651 and mild steel has been investigated. The experimental study has been done on compact tension specimen and tensile specimen of both materials at different cross-head speeds. The effect of increased cross-head speed is found to increase yield strength properties and to reduce the fracture toughness values of aluminium alloy and mild steel. Numerical modelling using finite element software LUSAS has been done and well predicted the load versus crack mouth opening displacement of the specimen imposed with load. The results show that Stress Intensity Factor, J-integral and Crack Tip Opening Displacement at certain values of load applied can be found from the energy method.